HOUSING DELIVERY THROUGH PUBLIC PRIVATE PARTNERSHIP IN NIGERIA AND THE CASE FOR BENEFICIARIES’ INVOLVEMENT - Olumiyiwa B. Adeogun; Abraham A. Taiwo (Journal of Construction Project Management and Innovation)
Over the years successive governments have devised and launched strategies to tackle the huge housing deficit in Nigeria. In the recent past, public-private partnership was embraced and employed in a number of low-income housing schemes across the country. Four such schemes which represented a partnership between the state government and private developer, and between the federal government and private developer, were chosen as case studies. They are Sunshine Gardens and HOB Estate, both in Akure, the Doma Road Estate in Lafia and Shelter-View Estate in Ado Ekiti. The study sought to identify beneficiaries’ participation in the schemes. It was established that there was an absence of meaningful community/beneficiaries’ participation in these schemes. This absence of participation impinged on the overall performance of these shelter projects. A case was therefore made for beneficiaries’ participation in PPP arrangement for low-income housing in Nigerian cities. The advantage of having this third partner needs to be utilised to improve success on the present and future low-income housing schemes.